Erythropoietic Potential of CD34+ Hematopoietic Stem Cells from Human Cord Blood and G-CSF-Mobilized Peripheral Blood. (5th May 2014) - Jin, Honglian; Kim, Han-Soo; Kim, Sinyoung; Kim, Hyun Ok
Abstract : Red blood cell (RBC) supply for transfusion has been severely constrained by the limited availability of donor blood and the emergence of infection and contamination issues. Alternatively, hematopoietic stem cells (HSCs) from human organs have been increasingly considered as safe and effective blood source. Several methods have been studied to obtain mature RBCs from CD34+ hematopoietic stem cells via in vitro culture. Among them, human cord blood (CB) and granulocyte colony-stimulating factor-mobilized adult peripheral blood (mPB) are common adult stem cells used for allogeneic transplantation. Our present study focuses on comparing CB- and mPB-derived stem cells in differentiation from CD34+ cells into mature RBCs. By using CD34+ cells from cord blood and G-CSF mobilized peripheral blood, we showed in vitro RBC generation of artificial red blood cells. Our results demonstrate that CB- and mPB-derived CD34+ hematopoietic stem cells have similar characteristics when cultured under the same conditions, but differ considerably with respect to expression levels of various genes and hemoglobin development. This study is the first to compare the characteristics of CB- and mPB-derived erythrocytes. The results support the idea that CB and mPB, despite some similarities, possess different erythropoietic potentials in in vitro culture systems.